Non-conventional vascular accesses for the management of superior vena cava syndrome in patients with Intestinal Failure. Case series and systematic review. (October 2021) - Pérez Illidge, Luis Carlos; Ramisch, Diego; Valdivieso, León; Guzman, Carlos; Antoni, Diego; Rumbo, Carolina; Trentadue, Julio; Solar, Héctor; Gentilini, María Virginia; Gondolesi, Gabriel
Summary: Background: Type III Intestinal Failure (IF) is a devastating clinical condition.characterized by the inability of the gut to absorb necessary macronutrients, and/or water and electrolytes, requiring Parenteral Nutrition (PN) as chronic therapy. Long-term PN may lead to life-threatening complications; the loss of central venous access (LCVA) is the most frequent and challenging. To date, few studies in the literature have reported the relevance of Non-conventional Vascular Accesses (NCVA) in the management IF as part of the comprehensive multidisciplinary care. Methods: A retrospective analysis of a database collected from January 2006 to December 2019 was performed using SPSS v25.0 for statistical analysis, followed by a systematic review, using the PRISMA.methodology Results: From January 2006 to December 2019, 184 NCVA were placed in 71 patients with LCVA as IF-related complication; 173 were placed in 61 patients by interventional radiology (IR) and 11 NCVA were placed in 10 patients by the surgical team during the intestinal transplant (ITx) operation. From the 173 IR procedures 166 (95.9%) were successful with 3 ± 2.7 procedures/patient; average catheter permanence rate was 738.68 ± 997 days; complications related to the procedures occurred in 18/173 (10.4%), including two deaths. On the other hand, among the 11 NCVA implanted by the surgical team, 7 (64%) were successful and were safely withdrawn 30 days after ITx when were no longer needed; 2 (18%) catheters malfunctioned during the first week and could not be further used, and 1 was accidently removed; average catheter permanence rate was 26 ± 4 days. There was one complication (9%) requiring laparotomy; there was no mortality associated the procedure in this group. A systematic review was conducted to evaluate the success and safety of NCVA as part of the treatment of HPN-related complications; from 337, 542 papers, 14 studies were included. A total of 28 HPN-patients with LCVA received NCVA; 34 procedures were successfully performed, while procedure-related complications were reported in 11.7%, as well as one death. Conclusions: The data analyzed show that NCVAs may be successfully placed by expert teams, allowing to sustain long-term PN, as well as increasing the Intestinal Transplantation applicability for candidates in the extreme need of vascular access.